Measuring size evolution of distant, faint galaxies in the radio regime. Issue 3 (19th February 2018) - Lindroos, L; Knudsen, K K; Stanley, F; Muxlow, T W B; Beswick, R J; Conway, J; Radcliffe, J F; Wrigley, N
Abstract: We measure the evolution of sizes for star-forming galaxies as seen in 1.4 GHz continuum radio for z = 0–3. The measurements are based on combined VLA+MERLIN data of the Hubble Deep Field, and using a uv -stacking algorithm combined with model fitting to estimate the average sizes of galaxies. A sample of ∼1000 star-forming galaxies is selected from optical and near-infrared catalogues, with stellar masses M⊙ ≈ 10 10 –10 11 M⊙ and photometric redshifts 0–3. The median sizes are parametrized for stellar mass M * = 5 × 10 10 M⊙ as $R_{\rm e} = A× {}(H(z)/H(1.5))^{α _z}$ . We find that the median radio sizes evolve towards larger sizes at later times with α z = −1.1 ± 0.6, and A (the median size at z ≈ 1.5) is found to be $0. \!\!^{′′} 26± {}0. \!\!^{′′} 07$ or 2.3±0.6 kpc. The measured radio sizes are typically a factor of 2 smaller than those measure in the optical, and are also smaller than the typical H α sizes in the literature. This indicates that star formation, as traced by the radio continuum, is typically concentrated towards the centre of galaxies, for the sampled redshift range. Furthermore, the discrepancy of measured sizes from different tracers of star formation, indicates the need for models of size evolution to adopt a multiwavelength approach in the measurement of the sizes star-forming regions.